Combination of Soxhlet extraction and catalytic hydrodebromination for remediation of tetrabromobisphenol A contaminated soil. (August 2022) - Su, Heng; Li, Peng; Wang, Yanfei; Wu, Haiyang; Ma, Xuanxuan; Liu, Ying; Ma, Yunbo; Liu, Sujing; Xia, Chuanhai
Abstract: As a widely used brominated flame retardants (BFRs), tetrabromobisphenol A (TBBPA) has been detected in various environmental matrices and is known to cause negative effects on both the environment and human health. In this study, a combined method was developed for the abatement of TBBPA contaminated soil based on successive steps of solvent extraction (SE) and catalytic hydrodebromination (HDB) over Pd/C. The results showed that TBBPA could be efficiently extracted from the TBBPA contaminated soil with polar solvents. Subsequently, TBBPA could be completely hydrodebrominated over Pd/C in ethanol, via multistep ultimately yielding bisphenol A. Moreover, NaOH, NH3 H2 O, and Et3 N were more favorable to promote the HDB of 4-TBBPA over Pd/C, and 100% bromide atom removal ratio of TBBPA was achieved within 40 min when [NaOH]0 /[organic-Br]0 was more than 1.10 in ethanol. However, the catalytic activity of Pd/C decreased with the repeated use in ethanol. To study the mechanism for this phenomenon, fresh and used catalysts were analyzed by characterization techniques including scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), and energy dispersive X-ray spectrometer (EDS). It was found that the deactivation of Pd/C catalyst caused by the gradual accumulation of NaBr could be recovered by washing with water. On the basis of these studies, an effective and practical system for the combined method of SE and catalytic HDB over Pd/C was developed to dispose BFRs contaminated soils. Graphical abstract: Image 1 Highlights: A combined method of SE and catalytic HDB is developed to dispose contaminated soil. Ethanol is the best solvent for the combined method of SE and catalytic HDB. The base influences the activity and stability of catalysts in HDB reaction. The mechanism of this phenomenon is investigated by characterization analyses. The combined method is applicable to efficient abatement of BFRs contaminated soil.